Freedom of expression and the metaverse: on the importance of content creation for the emergence of a complex environment - Fornasier, Mateus de Oliveira (Revista de Investigações Constitucionais, 2023)
This research analyzes the importance of the freedom of expression in the creation of the metaverse, in a context of increasing power of Big Techs in the digital environment. As its results, technical knowledge related to many areas and creativity are fundamental for the creation of the metaverse. Thus, its creation must be democratized. Public policies ensuring ways to access content creation must be developed, and such a democratization must be based on freedom of expression. And limitations to the exercise of such freedom must not be subjected to private interests of huge corporations, nor moderated solely by technological tools. Methodology: hypothetical-deductive method of procedure, with a qualitative and transdisciplinary approach, and a bibliographic review research technique.